Profil Asam Lemak Minyak Ikan Sardine sebagai Sumber Omega 3 - Kristina Haryati (Universitas Mataram, 2024)
Sardines, or lemurs fish, is a type of pelagic fish commonly found in the waters of the Bali Strait, with high oil content but low quality, although it still contains important elements for health such as omega 3. This research aims to identify the fatty acid profile of sardine fish oil as a source of omega 3 before and after purification. The method used in this research is divided into two parts: purification and testing of fatty acid profiles. The purification process is divided into 3 stages: degumming with citric acid, neutralizing sodium hydroxide (NaOH), and whitening using 5% magnesol XL. Fatty acid profile testing is divided into 3 stages: fatty acid extraction, methyl ester formation, and fatty acid identification. The results showed that the percentage of Saturated Fatty Acids (SFA) in crude oil and pure oil was 30.06% and 22.85%, respectively; for Monounsaturated Fatty Acids (MUFA), it was 11.84% and 8.83%, while multi-chain unsaturated fatty acids (PUFA) were 24.46% and 21.52%. The percentage of omega 3 in crude fish oil and pure oil is 20.89% and 14.87%, respectively; omega 6 is 3.35% and 6.53%; and omega 9 is 6.15% and 5.24%. These findings show that PUFA has a significant percentage after SFA, and the highest PUFA content is omega 3, especially Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA). Thus, this research shows that pure fish oil has the potential to be further developed into products rich in omega 3.